Study the Effect of Face Sheets Material on Strength of Sandwich Plates with Circular Hole - Hatem Rahem Wasmi; Nawal Falkhous Eshaut (Journal of Engineering, 2023)
This study aims to investigate the effect of changing skins material on the strength of sandwich plates with circular hole when subjected to mechanical loads. Theoretical, numerical and experimental analyses are done for sandwich plates with hole and with two face sheet materials. Theoretical analysis is performed by using sandwich plate theory which depends on the first order shear deformation theory for plates subjected to tension and bending separately. Finite element method was used to analyse numerically all cases by ANSYS program.